2017
DOI: 10.21500/20112084.2040
|View full text |Cite
|
Sign up to set email alerts
|

Personality and Emotion Regulation Strategies

Abstract: The emotions has many important functions in our life such as in relation of interpersonal communication, and health. In interpersonal communicative function aimed to signal to other information about internal state. Emotions manifests in specific cognitive, behavioural, and physiological reactions, thus closely related to health. There is wide variety of ways for individuals to regulate their emotion. In this regard, there are two kinds of emotion regulation strategy; first Antecedent-focused emotion regulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 18 publications
5
16
0
3
Order By: Relevance
“…Neuroticism, among the Big Five traits, has the strongest connection with emotion regulation abilities (Gross & John, 2003), as it is the trait that is most directly related to the emotional sphere. Moreover, neuroticism seems to be positively related with the use of ineffective ways of regulating emotions (Gross & John, 2003;Purnamaningsih, 2017;Wang, Shi, & Li, 2009). Also, in our study, we obtained a negative significant correlation between neuroticism and using reappraisal and a positive significant correlation between neuroticism and using suppression.…”
Section: Discussionsupporting
confidence: 66%
“…Neuroticism, among the Big Five traits, has the strongest connection with emotion regulation abilities (Gross & John, 2003), as it is the trait that is most directly related to the emotional sphere. Moreover, neuroticism seems to be positively related with the use of ineffective ways of regulating emotions (Gross & John, 2003;Purnamaningsih, 2017;Wang, Shi, & Li, 2009). Also, in our study, we obtained a negative significant correlation between neuroticism and using reappraisal and a positive significant correlation between neuroticism and using suppression.…”
Section: Discussionsupporting
confidence: 66%
“…Extraversion has been found to correlate mainly with low suppression (John and Gross 2004;Purnamaningsih 2017;Wang et al 2009). This result seems to be consistent with the definition of extraversion, which implies that extraverts do not hide emotions and easily express their feelings (Eysenck 1967).…”
Section: Personality and Emotion Regulationsupporting
confidence: 75%
“…As for Big Five personality traits and emotion regulation, findings seem consistent across studies. Specifically, neuroticism was shown to be negatively correlated with reappraisal (Gross and John 2003;Purnamaningsih 2017;Wang et al 2009). John and Gross (2004) have suggested that emotionally stable individuals (those who were low in neuroticism) experience less negative affect and as a result do not have to deal with consequences of strong negative affect.…”
Section: Personality and Emotion Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, personality has been studied as a structural dimension of the psychology of the individual (Matthews, 2016;Linden, Dunkel, & Petrides, 2016;Revelle, 2016) and emotions are understood as a set of events that arise at the level of psychological description constituted by neurobiological processes, with holistic empirical approach (Barrett, Mesquita, Ochsner, & Gross, 2007;LeDoux, Phelps, & Alberini, 2016;Purnamaningsih, 2017;LeDoux & Brown, 2017) that are related to SA, perception, cognition and personality (Pessoa, 2018), which should be approached comprehensively (Cowen & Keltner, 2017) in the interaction with the school context in which the student develops (Scott-Parker, 2017) and the way in which together with the Personality modulates attention (Mogg & Bradley, 1999).…”
Section: Studies On Personality Emotion and Hrvmentioning
confidence: 99%